OPPORTUNITIES OF DIGITAL TECHNOLOGIES (Academicia Globe: Inderscience Research, 2022)
Digital technologies are driving new ways of working and thinking while opening-up opportunities that we could not have imagined. For instance, it can assist policymakers to better understand how our natural world -- such as forests, coral reefs, or glaciers -- are changing in real-time and where to take action. Look at UNDP’s Data Futures Platform for example, it provides policymakers with the latest data and analytics to inform key areas like vaccine inequity